Gastroparesis in Adolescent Patient with Type 1 Diabetes: Severe Presentation of a Rare Pediatric Complication - Fortunato Lombardo; Bruno Bombaci; Stefano Costa; Mariella Valenzise; Nino Giannitto; Davide Cardile; Sergio Baldari; Giuseppina Salzano; Stefano Passanisi (Galenos Yayincilik, 2024)
Gastroparesis is a long-term complication of diabetes related to autonomic neuropathy. It is characterized clinically by delayed gastric emptying and upper gastrointestinal symptoms, including early satiety, postprandial fullness, nausea, vomiting, and abdominal pain. Gastric emptying scintigraphy is the gold standard for diagnosis as it reveals delayed gastric emptying. Therapeutic strategies include dietary modifications, improvement of glycemic control, and prokinetic drugs. Case descriptions of diabetic gastroparesis in pediatric ages are very scarce. We report the case of a 16-year-old adolescent with severe presentation of diabetic gastroparesis. She presented with recurrent episodes of nausea, vomiting and abdominal pain which led progressively to reduced oral intake and weight loss. Her past glycemic control had been quite brittle, as demonstrated by several hospitalizations due to diabetic ketoacidosis and recurrent episodes of severe hypoglycemia. After the exclusion of infectious, mechanical, metabolic, and neurological causes of vomiting, a gastric emptying scintigraphy was performed, leading to the diagnosis of gastroparesis. Treatment with metoclopramide was started with progressive relief of symptoms. To improve glycemic control, insulin therapy with an advanced hybrid, closed loop system was successfully started. Pediatricians should consider diabetic gastroparesis in children and adolescents with long-standing, poorly controlled diabetes and appropriate symptomology.